1997
DOI: 10.1002/j.1550-8528.1997.tb00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Drug Treatment of Obesity in a Private Practice Setting

Abstract: ATKINSON, RICHARD L, ROY C BLANK, DONALD LAS L RITCH. Long-term drug treatment of obesity in a private practice setting. Obes Res. 1997;5:57&586. This study evaluated the long-term efficacy and safety of the combination of phentermine and fenfluramine for the treatment of obesity in a private practice setting. A total of 1388 consecutive, qualified patients presenting to a private general internal medicine practice in Charlotte, NC, were enrolled with eligibility criteria including: age 18 years to 60 years, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…However, overwhelming majority of studies has shown that mono drug therapy may not be enough to reach patient targets. Some investigators have suggested that greater weight loss might be achieved by combining the anti-obesity drugs [26,35] as they have different mechanisms of actions. Recently, Wadden et al [36] reported that the addition of orlistat to sibutramine did not induce further weight loss when compared to treatment by sibutramine alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, overwhelming majority of studies has shown that mono drug therapy may not be enough to reach patient targets. Some investigators have suggested that greater weight loss might be achieved by combining the anti-obesity drugs [26,35] as they have different mechanisms of actions. Recently, Wadden et al [36] reported that the addition of orlistat to sibutramine did not induce further weight loss when compared to treatment by sibutramine alone.…”
Section: Discussionmentioning
confidence: 99%
“…reported a 15.9% weight loss in the first 34 weeks of treatment with phentermine-fenfluramine using three times the dosage of fenfluramine (60 mg per day) compared to the 20 mg per day used in our five cases. Other studies (Blackburn & Kanders, 1987;Atkinson, Blank, Schumacher, Levine, & Ritch, 1993;Bray, 1995;Goldstein & Potvin, 1994;Weintraub, 1992; have utilized from 20 to 120 mg of fenfluramine per day. Using a lower dose may decrease the frequency or severity of side effects and is more cost effective.…”
Section: Discussionmentioning
confidence: 97%
“…In light of these considerations, the opinion of polypharmacy has risen. 19,20,23 In this connection, an additional effect of metformin plus orlistat therapy on weight loss and insulin resistance is expected. Surprisingly, on the contrary to our hypothesis, the combination of metformin and orlistat therapy did not significantly induce greater weight loss and decrement on insulin resistance as compared to orlistat alone.…”
Section: Discussionmentioning
confidence: 99%